Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas. Issue 7 (2nd July 2016) - Lyu, Yong; Ding, Fan; Sun, Jie; Xu, Peng-Peng; Hu, Jie-Ying; Xie, Shao-Yu; Li, Kai-Chun; Chang, Hong-Wei; Qin, Wei; Yu, Liang; Xie, Hua; Li, Guang-Jiang; et al.
Abstract: Background : To determine the seroprevalence, latent infection rate and risk factors for severe fever with thrombocytopenia syndrome virus (SFTSV) infection, a cross-sectional study was conducted in the general population of the Western region of Anhui Province of China from 1 September to 31 December 2014. Methods : Twelve villages with the highest rates of endemic SFTS infection were selected from six towns in two counties in the western region of Anhui Province. Blood samples were collected and tested for the presence of SFTSV-IgG antibodies by ELISA. Each participant was interviewed using a structured questionnaire before blood collection. Participants with seropositive specimens were further investigated using another structured questionnaire. Results : Of 2126 blood specimens collected, 99 (4.66%) were seropositive for SFTSV. None of the participants had been diagnosed with SFTS before the blood collection or were accompanied by fever, thrombocytopenia and leukocytopenia after blood collection. Multivariate logistic regression model analysis revealed living in areas of uncontrolled vegetation growth, long-term residents of the locality and tick bites as high risk factors for SFTSV infection. Conclusions : The overall seroprevalence of SFTSV is higher in the western region of Anhui, possibly due to latent infection, with the main risk factors being living in areas of uncontrolled vegetation growth, long-term residents of the locality and tick bites. Further investigations are warranted to clarify the modes of SFTS virus transmission, while vector management, education on tick bite prevention and personal hygiene management should be implemented for high risk groups in endemic areas.